2012
DOI: 10.1016/j.bbadis.2011.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Berberine protects against high fat diet-induced dysfunction in muscle mitochondria by inducing SIRT1-dependent mitochondrial biogenesis

Abstract: Berberine (BBR) has recently been shown to improve insulin sensitivity in rodent models of insulin resistance. Although this effect was explained partly through an observed activation of AMP-activated protein kinase (AMPK), the upstream and downstream mediators of this phenotype were not explored. Here, we show that BBR supplementation reverts mitochondrial dysfunction induced by High Fat Diet (HFD) and hyperglycemia in skeletal muscle, in part due to an increase in mitochondrial biogenesis. Furthermore, we ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(101 citation statements)
references
References 56 publications
8
91
1
1
Order By: Relevance
“…The results obtained in these animal models are mostly in agreement with those obtained in human studies. The most used protocol to induce insulin resistance is overfeeding with high-fat/high-sugar diets in rats (Chanseaume et al 2006, Gomes et al 2012, Crescenzo et al 2013, Warren et al 2014 or 233:1 in mice (de Wilde et al 2008, Shelley et al 2009, Yuzefovych et al 2013, however, models of genetic obesity were also used (Holmström et al 2012). However, other observations report discrepant results, showing that high-fat feeding in rats was associated with no variation (Atgié et al 1993, De Feyter et al 2008a or even a higher mitochondrial capacity (Hancock et al 2008), and IR could be related to incomplete intramitochondrial β-oxidation (Koves et al 2008).…”
Section: Mitochondrial Dysfunction In Insulin Resistancementioning
confidence: 99%
“…The results obtained in these animal models are mostly in agreement with those obtained in human studies. The most used protocol to induce insulin resistance is overfeeding with high-fat/high-sugar diets in rats (Chanseaume et al 2006, Gomes et al 2012, Crescenzo et al 2013, Warren et al 2014 or 233:1 in mice (de Wilde et al 2008, Shelley et al 2009, Yuzefovych et al 2013, however, models of genetic obesity were also used (Holmström et al 2012). However, other observations report discrepant results, showing that high-fat feeding in rats was associated with no variation (Atgié et al 1993, De Feyter et al 2008a or even a higher mitochondrial capacity (Hancock et al 2008), and IR could be related to incomplete intramitochondrial β-oxidation (Koves et al 2008).…”
Section: Mitochondrial Dysfunction In Insulin Resistancementioning
confidence: 99%
“…In healthy male subjects, high-fat feeding for 3 days was sufficient to reduce mRNA levels of PGC1α, PGC-1β and several other mitochondrial genes in skeletal muscle [107]. Similarly, genetic, or high-fat diet-induced obesity and insulin resistance in rodents has been reported by several groups to reduce mitochondrial gene expression, protein expression and mitochondrial respiration in skeletal muscle [107][108][109][110][111]. Providing additional evidence of a link between mitochondrial dysfunction and insulin resistance is the fact that antiretroviral therapy used to suppress human immunodeficiency virus infection causes insulin resistance in association with mtDNA copy number [112].…”
Section: Mitochondrial Dysfunction In Muscle and Its Association Withmentioning
confidence: 95%
“…Gomes et al completed a 12 week HFD study and found declines in mitochondrial enzymatic and molecular signaling activity, but used a similar diet to Lionette and colleges at 60% energy intake coming from lipids (24). This finding suggests that length of the HFD and chronic ingestion of lipids is the main contributor to metabolic syndrome.…”
Section: Differences In Metabolic Functionmentioning
confidence: 99%
“…However, long term manipulations of a HFD have shown the opposite effects on AMPK, with a decline in activity (24). Chronic ingestion of a high fat diet is well known to cause insulin insensitivity.…”
Section: High Fat Diet and Skeletal Musclementioning
confidence: 99%
See 1 more Smart Citation